KEJAHATAN TERHADAP PERKAWINAN (PERKEMBANGANNYA DALAM HUKUM PIDANA POSITIF INDONESIA) - Priyambodo, Rio Anggoro; Kuswardani, Kuswardani (Jurnal Yustisiabel, 2023)
The crime against marriage is for anyone who holds a marriage when knowing that marriages or marriages that have existed become a barrier to the legality of the marriage. Therefore, it is important to review a positive criminal law in Indonesia regarding crimes against marriage. This research is an empirical juridical research that then the data will be analyzed in a cailiative-normative manner, examining by interpreting by inferring the data contained in the statutory documents. In qualitative methods, it is built on secondary data in the form of theory, meaning and substance from various literatures and laws and regulations so that conclusions are reached. The results showed that crimes against marriage based on the Criminal Code in positive criminal law in Indonesia, namely crimes and violations are threatened with punishment which is suffering or torture for the person concerned. However, there are still types of crimes regulated outside the Criminal Code, known as "special crimes" such as corruption, subversion, narcotics, economic crimes. Violation is a minor criminal act, the threat of punishment is in the form of a fine or confinement. All criminal acts that are classified as violations are regulated in book III of the Criminal Code. Crimes against marriage based on Islamic law, namely in Islam when someone commits a crime, there must be criminal responsibility. Islam divides the two in regulating Islamic criminal punishment, first jarimah hudud which is the punishment given to criminal perpetrators in accordance with the Qur'an and hadith. The two jarimah takzir, namely the criminal sanctions imposed on criminals are not contained in the Qur'an and this hadith of punishment is determined by the ruler.